(untitled) (Práxis Educativa, 2020)
The purpose of this paper is to contribute to the debate concerning homeschooling in Brazil, through a theoretical essay. In this sense, on the one hand, the main arguments in favor of the practice are presented; and, on the other hand, aspects that support the school as a space for the possibility of recognizing difference and equality. It is important to reflect on the relevance of the relationship with the other for the construction of knowledge. Thus, this text relies on Vygotsky and the concept of Proximal Development Zone coined by him. In conclusion, the importance of a broad, solid debate is considered, in which the family, social and cognitive specificities of each child are considered with regard to the planning and action of measures involving education in Brazil. Keywords: Homeschooling. Difference. Knowledge building. Learning. Vygotsky.